A decade of experience in the exercise of the National Health Authority’s regulatory function: Peru 2006 - 2015 - Robles–Guerrero, Luis Ricardo (2017)
This paper discusses the changes to the rulemaking process performed by the National Health Authority (ANS) during a decade, as an expression of the exercise of its health-related regulatory function. Before the implementation of said changes, the initiative for rulemaking was freely taken by the proposing entities. This situation led to an increased risk of mistakes, and the lack of a standardized methodology and an organized structure of the Regulatory Documents (DN) to be approved by the Ministry of Health. As a result, the National Health Authority decided to organize and standardize the process, in order to reduce the risk of mistakes during such rulemaking process. Based on the revision of the health-related rulemaking performed by the Ministry of Health for the period 2006 - 2015, which was published on the Legal Standards supplement of El Peruano official gazette, the legal standards (supreme decrees, supreme resolutions) and regulatory documents (health-related technical standards, directives, among others) approved by ministerial resolution are included herein. The statistical analysis of the rulemaking allows its classification by subject, document type and year for comparison purposes. The experience shows that 88 health-related technical standards, 64 health-related directives, 151 administrative directives, 89 technical guidelines (including 40 clinical practice guidelines) and 156 technical papers were approved. Besides, the rulemaking process performed by the ANS was more organized and safer, presented less risk of mistakes, and had a scientific technical support that strengthened the exercise of the sectorial stewardship.